Creative producing : keep mum (short film) - Nur Farreha Abdul Jalil (2015)
Keep Mum: Short Film (Narrative) - “Keep Mum” is a short film about a husband and father called Shen, who is constantly abused by his wife but he doesn’t seek help due to his unspoken love for his family."